The effect of experimental diets incorporating fermented soybean meal on growth metrics and utilization of nutrients in broiler chickens - Ncube, Nqobani; Mawere, Cephas (International Journal of Sustainable Agricultural Research, 2024)
The aim of this study was to explore the impact of fermented soybean meal (FSBM) on the nutritional quality of feed, growth performance indicators, and nutrient utilization in broiler chickens, aiming to overcome the challenges associated with locally produced soybean meal stemming from anti-nutrients and variations in nutritional quality. The study methodology included assessing growth performance metrics through two-way ANOVA statistical analysis and evaluating nutrient utilization in broiler chickens. Results indicated that broiler chickens fed with FSBM exhibited superior performance, displaying the highest average weekly weight gain (452 grams), optimal feed conversion ratio (1.39), extended intestinal length (225 cm), increased intestinal weight (297.5 grams), and heightened activity of digestive enzymes compared to other treatment groups throughout the feeding trials. The results of this study suggest that FSBM’s better digestibility helps broiler chickens grow faster. This makes it a possible replacement for animal protein sources like fish meal in poultry feed production, which is good for both local poultry feed producers and consumers.